Teachers’ and community stakeholders’ perceptions about school – community relations in Cyprus - Anaxagorou, George (International Journal about Parents in Education, 2023)
This paper describes the findings of a comparative study of rural and urban communities in Cyprus concerning the perceptions of primary school teachers and community stakeholders as regards school–community relations. The data were collected via a semi-structured interviewing technique amongst primary school teachers and community stakeholders. The analysis of the qualitative data demonstrates that both primary teachers and community stakeholders whether in a rural or an urban area consider school– community cooperation as a positive and important factor in their respective spheres of interest. However, teachers were found to maintain a more conservative stance towards relationships with the local community, believing that their professional autonomy is threatened by interferences of community stakeholders and agents. Furthermore, there was a divergence of perceptions between rural participants and their urban counterparts as regards to the extent to which such a cooperation should take place; both teachers and community stakeholders in rural areas seemed to be more willing to extend their communication and their relations in additional fields. On the contrary, teachers and community stakeholders in urban sites seemed more conservative towards such a situation; they regard that such a cooperation and such relations should be limited. The findings come to validate similar findings reported in the limited literature in Cyprus (Georgiou, 1998; Symeou, 2002) and indicate that there is a lot of ground to be covered towards extending and improving school–community relations for the benefit of all institutions concerned.